American interests in the African continent after 2000 - Researcher Jihad Abbas Ali, Assistant Professor Dr. Ziyad Youssef Hamad (The college of law and political science journal, 2023)
The United States of America has established its military bases in the Africancontinent with the aim of increasing its control over the resources of the continent.It has spread its culture and policy there in order to control the African leaders soas to control it. American companies hastened to dominate African wealth underthe pretext of raising the level of the African economy.The United States of America is one of the most prominent countries interestedin the African continent, and this interest is governed by several factors, political,economic, military and security, so achieving one of them helps to achieve its otherinterests and this leads to an increase in its power.At the beginning of the twentieth century and the international changes thataccompanied it, the nature of relations between states became competitive, in orderto secure states for their interests in all aspects and in all parts of the world, and themost prominent of these major states is the United States of America, and the mostprominent regions of the world is the African continent, especially since it is oneof the most important areas that received American attention because of its wealthand its multiple interests in it Therefore, these factors will be discussed in twoUHTXLUHPHQWV7KHÀUVWUHTXLUHPHQWLVWRFODULI\WKHSROLWLFDODQGHFRQRPLFIDFWRUVand the second requirement is about American military and security interests in theAfrican continent.